Macrozoobenthos community structure as an indicator of water quality on the coast of Sungai Pakning Village, Bukit Batu District, Bengkalis - Kusdiatmoko, Aprizal; Nasution, Syafruddin; Yoswaty, Dessy (Science, Technology, and Education Care, 2024)
Sungai Pakning is a sub-district and the capital of Bukit Batu District, Bengkalis Regency, which has an area of ​​34 km2. The Pakning River is widely used for tourism, ship transportation, ship landings, and settlements, potentially disrupting the aquatic ecosystem's balance. This research aims to determine the structure of the macrozoobenthos community and the status of the water quality conditions of the Pakning River. This research was carried out in August – September 2023 using a purposive sampling technique with three stations. There are 9 (nine) macrozoobenthos species, namely Nerita polita, Unosalpinx cinerea, littorina melanostoma, Telescopium telescopium, Indothais gradata, Cheritiea obtusa, Natrica trigina, Achatinella mustelina, and Uca sp. The abundance of macrozoobenthos is 20,400 ind/ha. The relative abundance of macrozoobenthos is 34.56%. Calculated biodiversity index (H'= 1.62), uniformity index (E= 0.59), and dominance index (C= 0.25). The ANOVA test results showed that the abundance of macrozoobenthos between stations obtained a significant value of 0.656 where (p > 0.05). The results of the ANOVA test for the abundance of macrozoobenthos between subzones obtained a value of 0.521, where (p > 0.05). Water quality measurements in Pakning River waters obtained temperature values ​​of 27-28°C, water pH 7, and salinity ranging from 30-31‰. The average sediment organic matter ranges from 26.40% -32.58%, and the dominant sediment type is muddy. The research results show that water conditions are still within normal limits and support the survival of macrozoobenthos